Carbon nanotube-based microwave resonant sensor for organic contaminants detection - Mohammadi, Ahmad (2014)
Organic contaminants are one of the most important kinds of environment pollutions which have been raised over the last century. Conventionally organic contaminants are measured using various methods which require extraction, cleaning procedures and organic solvent. These methods are time consuming and expensive. Fast and accurate detection of organic compounds is the important key to protect the environment and human health safety. Napropamide and phenolic compounds are two kinds of organic contaminants in the Malaysian environment which are chosen to be investigated in this thesis. This thesis describes the design of proximity coupled feed patch antenna as an organic contaminates sensor. This sensor system consists of a two-layer Flame Retardant (FR-4) patch antenna coated with Multi Walled Carbon Nanotubes (MWCNTs) and Polypyrrole-Chitosan (PPy-CHI) for absorbing organic contaminates. Proximity coupled feeding was chosen to feed the patch antenna and the feeding is from the ground plane side without any physical contact to the material under test. The best design of patch antenna and feed line position in 5 GHz resonant frequency are chosen based on simulation results using full-wave electromagnetic simulator Computer Simulation Technology (CST) Microwave studio. The performance of the fabricated patch antenna was tested using Vector Network Analyzer (VNA) and the results are then be compared with simulations results. Multi Walled Carbon Nanotubes (MWCNTs) and Polypyrrole-Chitosan (PPy-CHI) as a sensing layer were coated on the top of antenna using electric field deposition. Atomic Force Microscopy (AFM) was used to ensure successful coating result on the top of the antenna. Chemical interaction between applied materials to the sensing layer was investigated by Fourier Transform Infrared Spectroscopy (FT-IR). The whole system after coating and fabrication was tested using different amounts of phenol, 2-4 Dichlorophenol (24DCP), commercial napropamide and napropamide at room temperature (25oC). Changes in resonant frequency of patch antenna before and after applying phenol, 2-4 Dichlorophenol (24DCP), commercial napropamide and napropamide were measured. Based on measurement results, FR-4 patch antenna coated with MWCNTs and PPy-CHI are capable to detect small concentration of measured materials down to 0.5 ppm. At this operating frequency (5 GHz), the technique can be used in wireless network sensor systems to measure organic pollutions vapour in shielded area for future research.